If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(-2-3x)=66
We move all terms to the left:
-6(-2-3x)-(66)=0
We add all the numbers together, and all the variables
-6(-3x-2)-66=0
We multiply parentheses
18x+12-66=0
We add all the numbers together, and all the variables
18x-54=0
We move all terms containing x to the left, all other terms to the right
18x=54
x=54/18
x=3
| -2(6y+2)+9y=35 | | 10(1+3b=-20 | | (x-1/2)^2=49/4 | | 2x/3-2=x+6 | | B+6=10+7b-4b | | 4a=7a-96 | | r^2=5+4r | | 2x-9+x-8=8 | | 1/3(18y-6)=-5/6(12-4y) | | 3/5=5/7+y | | -4(1-5s)=21 | | 5x-8=18+5x | | -(4x-4)+20=44 | | 3(4g+6)=2(g+9) | | 4(1+6b)+6=-134 | | X+2/3p+1/2p=234 | | 1.06g-3=0.719 | | 3/5=5/7+x | | 6b-7=7-6b | | 3x+21=2x-6=50 | | 110=5(7x-2)+5x | | h/6−1=3 | | 10x+24=6x+72 | | 15(-x-3)=12(x+2) | | −3+5v=−38 | | 3/5=5/7=x | | 4c-(2c+3)=7 | | 5x-3x+14=x+8 | | 2(x+1)-(5+x)=-4 | | C=2•3.14r | | 2x+1+x+11=27 | | |-(x-5)|=8.5 |